You don't look fat, you look crazy - Longshore, Ashley uthor (Regan Arts, 2017)
"You Don't Look Fat, You Look Crazy is a window into the world of Longshore's irreverent, glamorous, and stunningly visual pop-art-filled life, where bedazzled flowers sit next to diamonds and Valium boxes, Jesus holds a black Amex and Wonder Woman dresses in Chanel. With tongue-in-cheek advice straight from her canvas, such as "There's No Crying At Bergdorf's," "Always Ask For More," and "What Would Blue Ivy Do," Ashley's honesty and DGAF attitude will grab you by your Givenchy lapels and hit you across the face with the donut you promised yourself you wouldn't eat. So be confident, grab life by the Birkins, embrace your "ambitchion," and remember, you don't look fat you look crazy!"